A STUDY OF SERUM LIPID PATTERN IN THALASSAEMIC PATIENTS - Tayyab, Muhammad; Abdullah, Muhammad; Ditta, Allah (Journal of Ayub Medical College Abbottabad, 2000)
Background: Thalassaemia is among the most common genetic diseases of man and the commonest inherited disorder in our country. This study was carried out to assess the lipid pattern in thalassaemic patients and to find out any significant variation in lipid pattern of these patients. Methods: Eighty thalassaemic patients (Group A) were selected from various blood transfusion centers and hospitals. Fifty, age and sex matched, normal controls (Group B) were also included in the study. 3.0 ml blood was drawn aseptically from the antecubital vein of each subject. The serum was separated and stored at 4°C till analysed. Serum total cholesterol (TC) and triglycerides (TG) of all the subjects were estimated using the commercially available kits. Results: There was a statistically significant difference (P<0.05) in the serum TC concentrations of thalassaemic patients as compared to those of normal controls. Scrum TG levels of thalassaemic patients were raised as compared to those of normal controls (though not statistically significant). Conclusion: There is a need to design a larger study to evaluate the real status of lipids and lipoprotein subtractions in thalassaemic patients.